PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP KECENDERUNGAN NARSISME PADA MAHASISWA TINGKAT I PROGRAM STUDI S-1 FARMASI FAKULTAS FARMASI DAN ILMU KESEHATAN UNIVERSITAS SARI MUTIARA INDONESIA - Sri Ramadhani; Sinarsi Meliala; Laksana Tobing; Epafroditus Sibuea (JURNAL PSYCHOMUTIARA, 2020)
This study aims to examine whether there is an influence of the use of Instagram social media on narcissistic tendencies carried out by students in the Bachelor of Pharmacy study program at Sari Mutiara Indonesia University in Medan. This study uses a quantitative approach. Data collection was conducted at the Sari Mutiara Indonesia University in Medan. The research subjects were students of Sari Mutiara Indonesia University in Medan with a sample of 42 people. The sampling technique of this study was purposive sampling. Data collection tool in the form of Instagram social media scale and narcissistic tendency scale. Test the validity of the instrument using the Corrected Item-Total Corelation test. Instrument reliability test was calculated using Alpha Cronbach formula. Data analysis uses a simple regression technique to test hypotheses with a significance value of 5%. The results showed that there was an influence between the use of Instagram social media on narcissistic tendencies in the students of the Bachelor of Pharmacy study program at Sari Mutiara Indonesia University Medan in the amount of 14.9%. The regression line equation is Y = 58,440 + 1,115 X. The conclusion of this study is that the use of Instagram social media for undergraduate students of Pharmacy Program at Mutiara Mutiara University in Medan Medan is in the high category, narcissistic tendency in the students of the S-1 Pharmacy Study Program at Sari Mutiara University Indonesia Medan is in the low category.